Ties that Bind : Race and the politics of friendship in South Africa - Soske, Jon (Book collections on Project MUSE., 2016)
"What does friendship have to do with racial difference, settler colonialism and post-apartheid South Africa? While histories of apartheid and colonialism in South Africa have often focused on the ideologies of segregation and white supremacy, Ties that Bind explores how the intimacies of friendship create vital spaces for practices of power and resistance. Combining interviews, history poetry, visual arts, memoir and academic essay, the collection keeps alive the promise of friendship and its possibilities while investigating how affective relations are essential to the social reproduction of power. From the intimacy of personal relationships to the organising ideology of liberal colonial governance, the contributors explore the intersection of race and friendship from a kaleidoscope of viewpoints and scales. Insisting on a timeline that originates in settler colonialism, Ties that Bind uncovers the implication of anti-Blackness within nonracialism, and powerfully challenges a simple reading of the Mandela moment and the rainbow nation. In the wake of countrywide student protests calling for decolonization of the university, and reignited debates around racial inequality, this timely volume insists that the history of South African politics has always already been about friendship. Written in an accessible and engaging style, Ties that Bind will interest a wide audience of scholars, students, and activists, as well as general readers curious about contemporary South African debates around race and intimacy"--Amazon.